A kind of micro-porous adhesive layer added manganese carbon composite material aldehyde removal plywood and its preparation method

CN122938918APending Publication Date: 2026-10-20ZHEJIANG SHENGHUA YUNFENG GREENEO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610988390.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-03
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

发泡改性虽可改善透气性,但常规直接混料方式往往带来胶层结构松散、力学和耐水性能下降、氨气异味以及固化剂被造孔剂消耗等一系列衍生问题

Benefits of technology

[0012]1. 依托包覆耦合结构实现的原位造孔供氧,板材24h甲醛去除率可达91.7%;60℃加速老化24天后,月均除醛衰减速率较传统无微孔锰炭板材更低。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This application provides a formaldehyde-removing plywood with a microporous adhesive layer and a manganese-carbon composite material, and its preparation method, belonging to the field of engineered wood products manufacturing technology. Existing manganese-carbon modified plywoods have a dense structure and internal oxygen deficiency after the adhesive layer cures, leading to rapid deactivation of the manganese-carbon catalytic sites and a significant decline in formaldehyde removal performance over time. This application uses a manganese-carbon-resin pre-coated sodium bicarbonate coupled granulation process as a solution. By controlling the pores created by sodium bicarbonate, gas transport channels are constructed within the adhesive layer to alleviate the oxygen deficiency problem. Simultaneously, the controlled pore design avoids the loose adhesive layer structure and reduced water resistance caused by directly adding foaming agents. This process can be directly adapted to existing production lines, improving the long-term formaldehyde removal capability of the plywood while maintaining its mechanical and water resistance properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of functional modification manufacturing technology for engineered wood products, and in particular to a modified plywood with long-lasting formaldehyde removal based on a manganese-carbon-sodium bicarbonate coating coupling structure and its preparation process. Background Technology

[0002] Plywood is widely used in custom furniture and interior decoration. It is usually bonded with urea-formaldehyde resin adhesive, and its adhesive layer continuously releases free formaldehyde. By introducing manganese carbon material loaded with manganese dioxide into the adhesive layer, the formaldehyde is removed by the physical adsorption of activated carbon and the chemical catalytic degradation of manganese dioxide.

[0003] However, this solution has a structural problem: after the urea-formaldehyde resin is cured, the adhesive layer is dense and lacks gas diffusion channels. The manganese carbon material wrapped inside the adhesive layer is in a state of oxygen deficiency for a long time. The δ-MnO2 catalytic oxidation reaction gradually stops due to insufficient oxygen supply, and the adsorption sites of activated carbon are also easily saturated. As a result, the formaldehyde removal performance of the board will decline significantly in a short period of time.

[0004] To address the aforementioned oxygen deficiency issue, we attempted to add sodium bicarbonate as a pore-forming agent to the adhesive layer to construct a microporous, breathable structure. However, the conventional direct blending method presents new problems: upon direct contact between sodium bicarbonate and the ammonium salt curing agent, an ammonia-producing side reaction occurs at room temperature (NH4Cl + NaHCO3 → NH3↑ + CO2↑ + NaCl + H2O), consuming some of the curing agent and releasing ammonia gas, giving the board an odor that typically requires 2-4 months of room temperature curing to eliminate. Furthermore, the large, interconnected pores created by foaming disrupt the continuous cross-linking structure of the adhesive layer, leading to decreased bonding strength and water resistance. Summary of the Invention

[0005] The main problem this invention aims to solve is that the adhesive layer of existing manganese-carbon modified plywood becomes too dense after curing, resulting in insufficient internal oxygen supply. This makes it difficult for the δ-MnO2 catalytic reaction to proceed continuously, and the formaldehyde removal performance declines rapidly over time. Although foaming modification can improve air permeability, conventional direct mixing methods often lead to a series of derivative problems, such as a loose adhesive layer structure, decreased mechanical and water resistance properties, ammonia odor, and the consumption of curing agent by pore-forming agents.

[0006] This invention uses a high-viscosity mixed resin to coat sodium bicarbonate, thereby encapsulating pore-forming agent particles and forming a composite particle structure with a particle size of 200-800 μm. This composite particle structure undergoes thermal decomposition during hot pressing, forming micropores in situ around the catalytic sites. This avoids the reaction and consumption of sodium bicarbonate with the curing agent during direct blending, and simultaneously confines the formation of micropores to the vicinity of the catalytically active sites, achieving a synergistic coupling of pore-forming and catalytic processes in space. Constructing a composite particle structure where pore-forming and catalytic sites are close together links the oxygen supply and catalytic functions within the manganese-carbon adhesive layer at the microscopic level.

[0007] Specifically, manganese carbon material is first mixed evenly with urea-formaldehyde resin and a small amount of flour to obtain a mixed resin. Then, this mixed resin is thoroughly mixed with sodium bicarbonate at a mass ratio of 5-15:1, ensuring that the mixed resin completely coats the sodium bicarbonate particles. This mixture is then dried at a low temperature of 40-50°C to form composite particles. These composite particles are then added to the main adhesive solution, and finally, a curing agent is added. This process combines pore-forming and catalytic functions at the composite particle level. Simultaneously, the coating layer isolates the sodium bicarbonate from the curing agent, reducing curing agent consumption and minimizing issues such as insufficient curing and odor.

[0008] Ammonium chloride, accounting for 0.5-1% of the mass of the second urea-formaldehyde resin, is added to the mixed resin to allow partial pre-curing and cross-linking to occur during the low-temperature drying process at 40-50°C, forming a cured resin film with a certain degree of cross-linking. This film maintains its structural integrity during subsequent adhesive preparation and hot pressing, ensuring that sodium bicarbonate particles are effectively coated and isolated.

[0009] A formaldehyde-removing plywood with a microporous adhesive layer and a manganese-carbon composite material, comprising multiple layers of wood veneer and a microporous modified adhesive layer bonded between the veneers. The microporous modified adhesive layer is prepared from an adhesive, a manganese-carbon composite material, composite particles, and a curing agent; wherein the composite particles are formed by coating sodium bicarbonate with manganese-carbon-resin-flour and drying at low temperature, with a particle size of 200-800 μm; the adhesive layer also contains flour as a filler, with the total amount of flour being 30-40 wt% of the adhesive mass, a portion of which is contained in the composite particles, and the remainder added during the preparation of the main adhesive solution.

[0010] The microporous modified adhesive layer, through the synergistic control of hot-pressing process parameters and raw material ratios, forms a microporous structure within the adhesive layer resulting from the thermal decomposition of sodium bicarbonate. During hot-pressing, sodium bicarbonate decomposes to release CO2 gas, forming micropores within the adhesive layer. These micropores are located close to the manganese-carbon catalytic sites attached to the surface of the composite particles, facilitating oxygen diffusion inward and maintaining the catalytic activity of δ-MnO2. Simultaneously, a curing agent is added in the final step of adhesive preparation, and the sodium bicarbonate is isolated by the resin coating layer, preventing direct contact between the two at room temperature. This significantly reduces ammonia production side reactions and ensures efficient utilization of the curing agent. The presence of the microporous structure increases the gas permeability of the adhesive layer, but has limited impact on liquid water permeation. The water resistance of the adhesive layer mainly depends on the neutralization effect of Na2CO3 produced by the decomposition of sodium bicarbonate on residual HCl in the curing agent. This neutralization reaction brings the pH of the adhesive layer towards neutral, inhibiting the acid-catalyzed hydrolysis of urea-formaldehyde resin, thereby improving water resistance.

[0011] Compared with the prior art, the present invention has the following beneficial effects:

[0012] 1. Relying on the in-situ pore-forming oxygen supply achieved by the encapsulation coupling structure, the formaldehyde removal rate of the board can reach 91.7% in 24 hours; after 24 days of accelerated aging at 60℃, the monthly average formaldehyde removal decay rate is lower than that of traditional non-microporous manganese carbon boards.

[0013] 2. The dry bonding strength remains ≥1.0MPa, and the wet bonding strength can reach ≥0.90MPa after 24h immersion in cold water. The wet strength retention rate is about 90.0%~92.0%, which meets the requirement of ≥0.7MPa in GB / T 9846-2015.

[0014] 3. Because the coating layer isolates sodium bicarbonate from direct contact with the curing agent, the ammonia production side reaction is greatly reduced; when evaluating the odor according to GB / T 44689-2024, the odor level of normal boards is usually level 2, which can reach level 1 after adding manganese carbon, and the odor level of foamed manganese carbon boards can reach level 0, which is better than level 1 of ordinary manganese carbon boards.

[0015] 4. The core modification process only adds two steps: coating granulation and low-temperature drying, which is compatible with existing plywood production lines. Detailed Implementation

[0016] I. Testing Standards and Procedures

[0017] Formaldehyde removal rate and purification efficiency were determined according to JC / T 2761-2023. Bonding strength and water resistance were determined according to GB / T9846-2015 Class III plywood standard. Odor level of the boards was tested and evaluated according to GB / T 44689-2024 "Odor Classification and Evaluation of Wood-based Panels and Their Products," with odor levels recorded as integers 0, 1, 2, 3, and 4. Adhesive layer pH value was determined according to GB / T 14074-2017. Long-term aging was tested using multiple cycles according to JC / T 2761-2023. Adhesive viscosity was tested using a rotational viscometer at a constant temperature of 25℃. All tests included a single-variable control group, and the test results are expressed as specific measured values.

[0018] II. Detailed Description of Implementation Examples

[0019] The performance tests for the following embodiments were all performed in accordance with Section I, "Test Standards and Specifications": Formaldehyde removal rate and purification efficiency were determined according to JC / T 2761-2023; bonding strength and water resistance were determined according to GB / T 9846-2015 Class III Plywood Standard; the odor level of the board was tested and evaluated according to GB / T 44689-2024 "Odor Classification and Evaluation of Wood-based Panels and Their Products" and recorded as an integer level; the pH of the adhesive layer was determined according to GB / T 14074-2017; and the viscosity of the adhesive solution was tested at a constant temperature of 25°C using a rotational viscometer. Unless otherwise specified, each group had a single variable control, and the test results are expressed as specific test values.

[0020] Example 1: Preparation of manganese-carbon composite material

[0021] Coconut shell activated carbon with a particle size of 80-150 μm and a specific surface area of ​​approximately 1000 m² / g was selected, washed three times with deionized water, and dried at 90℃ for 18 h. A 0.05 mol / L potassium permanganate aqueous solution was prepared, and activated carbon was added at a mass ratio of 20:1 to potassium permanganate. Ethanol was added (ethanol to potassium permanganate molar ratio 2:1), and the mixture was stirred at 25℃ for 8 h. The mixture was filtered, washed with water until the pH of the filtrate reached 6-7, and dried at 70℃ for 10 h to obtain a manganese-carbon composite material with a δ-MnO₂ loading of 3.2 wt% (as determined by ICP-OES).

[0022] Example 2: Optimal Example

[0023] It uses 400mm×400mm×2.2mm eucalyptus veneer with a moisture content of 10.2%.

[0024] Urea-formaldehyde resin with a solid content of 52% and a viscosity of 4000 mPa·s was selected.

[0025] Use wheat flour.

[0026] Preparation of composite particles: 4g of manganese carbon composite material, 10g of urea-formaldehyde resin, 3g of flour and 0.1g of ammonium chloride were premixed in a paddle mixer at 200rpm for 8min. Then 1.3g of sodium bicarbonate was added and the mixture was continued at 100rpm for 20min (mixed resin: sodium bicarbonate ≈ 13:1, flour accounts for 17.6% of the mixed resin). The mixture was dried at 45℃ for 1.5h to obtain composite particles with a particle size of 200~800μm.

[0027] Preparation of the main adhesive solution: Mix the composite granules with 90g of urea-formaldehyde resin, add 34g of flour and stir well, and finally add 1.0g of ammonium chloride and stir evenly; after preparation, seal the adhesive solution and store it at a low temperature of 10-15℃, and use it within 24 hours.

[0028] The total proportions are: 100 parts urea-formaldehyde resin (10 parts for coating and 90 parts for the main adhesive), 4 parts manganese carbon, 1.3 parts sodium bicarbonate, 37 parts flour, and 1.1 parts NH4Cl.

[0029] Single-sided adhesive coating of 220g / m², seven layers of vertical texture assembly; cold pressing at room temperature for 2 hours at 0.6MPa; hot pressing at 0.6MPa for 45 minutes at 125℃ / min with a heating rate of 3℃ / min; during hot pressing, sodium bicarbonate decomposes to produce CO2, which forms a microporous structure in the adhesive layer; after cooling to room temperature, it is put into storage.

[0030] Finished product performance (data are specific test values): Dry bonding strength 1.06MPa, meeting the requirements of Class III plywood in GB / T 9846-2015; 24h formaldehyde removal rate / purification efficiency 91.7% (initial concentration 0.1mg / m³, determined according to JC / T 2761-2023); adhesive layer pH 6.3 (determined according to GB / T 14074-2017).

[0031] Example 3: Comparison of feeding methods and verification of curing agent compensation

[0032] All groups used the same eucalyptus veneer, urea-formaldehyde resin, and hot-pressing process (125℃, 0.6MPa, 45min), with only the feeding method or the amount of curing agent varying between groups. Dry bond strength, 24-hour formaldehyde removal rate / purification efficiency, and odor level of the boards were determined according to the aforementioned standards. Groups A, B, C, D, and F used direct mixing, meaning all components were added to the adhesive at once and stirred until homogeneous. Coating and dispersion refers to first coating sodium bicarbonate with manganese carbon, some resin, and flour to form composite particles, which were then dispersed in the remaining main adhesive solution.

[0033] Groups E and G use an encapsulation coupling process (same as in Example 2).

[0034] A: Blank Direct mixing 1.0wt% 1.01MPa 0.0% 2 B: Foaming only Direct mixing 1.0wt% 0.92MPa 8.4% 2 C: Manganese carbon only Direct mixing 1.0wt% 1.03MPa 87.6% 1 D: Direct compounding Direct mixing 1.0wt% 1.06MPa 86.8% 1 F: Direct compounding + reinforcement Direct mixing 1.3wt% 1.11MPa 87.6% 1 E: Enveloping coupling Dispersed after coating 1.0wt% 1.15MPa 91.3% 0 G: Encapsulation coupling + low solidity Dispersed after coating 0.8wt% 1.09MPa 88.7% 0

[0035] Note: The amount of 'NH4Cl' in the table is a percentage of the total mass of urea-formaldehyde resin; 'SB' in the following text refers to sodium bicarbonate.

[0036] In this table, the amount of NH4Cl refers to the first curing agent added to the main adhesive solution. The amount of the second curing agent in the preparation of composite particles is uniformly 0.5~1wt% of the mass of the second urea-formaldehyde resin.

[0037] All groups used the same eucalyptus veneer, urea-formaldehyde resin, and hot-pressing process (125℃, 0.6MPa, 45min), only varying the feeding method of each component or the amount of curing agent (NH4Cl). The specific definitions of each group are as follows:

[0038] Group A (blank control): No manganese carbon composite material or sodium bicarbonate (SB) was added; only urea-formaldehyde resin, flour, and curing agent were used. Group B (foaming only): Sodium bicarbonate (SB) pore-forming agent was added only; no manganese carbon composite material was added. Group C (manganese carbon only): Manganese carbon composite material was added only; sodium bicarbonate (SB) was not added. Group D (direct compounding): Manganese carbon composite material and sodium bicarbonate (SB) were directly added to the adhesive and mixed in one step. Group F (direct compounding + reinforcement): Based on the direct mixing in Group D, curing agent (N... The amount of H4Cl was increased from 1.0 wt% to 1.3 wt% to compensate for the consumption of curing agent by sodium bicarbonate; Group E (coating coupling, i.e. the present invention): sodium bicarbonate (SB) was pre-coated with manganese carbon-resin-flour to form composite particles, and then the composite particles were dispersed in the main adhesive solution; Group G (coating coupling + low solids): based on the coating coupling process of Group E, the amount of curing agent (NH4Cl) was further reduced to 0.8 wt% to verify the process robustness of the coating process under the condition of insufficient curing agent.

[0039] Group F was an improvement on Group D—the NH4Cl content was increased from 1.0 wt% to 1.3 wt% to compensate for insufficient curing agent due to SB consumption. Group G served as a control for Group E—the NH4Cl content was reduced to 0.8 wt% to verify whether the coating process still had advantages under conditions of insufficient curing agent. Odor rating results showed that normal boards were approximately level 2, while the addition of manganese carbon achieved level 1; the foamed manganese carbon sample reached level 0, superior to level 1 of ordinary manganese carbon boards; according to GB / T 44689-2024, which only uses integer levels, it was still recorded as level 1.

[0040] Results analysis:

[0041] (1) Group F (direct compounding + reinforcement 1.3wt%) vs. Group E (coating and coupling 1.0wt%): The bonding strength of Group E (1.15MPa) is higher than that of Group F (1.11MPa), the formaldehyde removal rate / purification efficiency (91.3%) is higher than that of Group F (87.6%), and the amount of curing agent used in Group E is lower (1.0wt% vs 1.3wt%). The two sets of data show that the superiority of the coating process does not only come from the fact that the curing agent is not consumed, but also from the microscopic morphological advantages brought about by the coating structure itself.

[0042] (2) Group G (coating coupling + low solids 0.8wt%) vs Group F (direct compounding + supplementary solids 1.3wt%): Group G, with only 62% of the curing agent used in Group F, still achieved a formaldehyde removal rate / purification efficiency of 88.7%, which is higher than Group F's 87.6%. Both Group E and Group G achieved an odor level of 0, which is better than the level 1 of ordinary manganese carbon boards, indicating that the foamed manganese carbon system has excellent low odor performance; the coating coupling process can also reduce the curing fluctuations caused by the consumption of curing agent by SB.

[0043] (3) The formaldehyde removal rate / purification efficiency of Group A (UF + flour + curing agent) was 0.0%, proving that the flour itself did not contribute to the formaldehyde removal effect under the test conditions. The formaldehyde removal rate / purification efficiency of Group B was 8.4%, which came from the small amount of physical adsorption of formaldehyde by the porous adhesive layer.

[0044] Example 4: Comparison of sodium bicarbonate addition gradients

[0045] Fixed conditions: 4 wt% manganese carbon, coating coupling process, 1.0 wt% NH4Cl; only the amount of SB added was changed in each gradient. Formaldehyde removal rate / purification efficiency in 24 hours was determined according to JC / T 2761-2023, adhesive strength was determined according to GB / T 9846-2015, and gel time was used as a process reference indicator.

[0046] 0wt% 1.03MPa 86.8% 351min 1.0wt% 1.13MPa 88.7% 374min 1.5wt% 1.07MPa 91.1% 386min 2.0wt% 0.99MPa 91.8% 403min

[0047] SB exhibits superior overall performance within the range of 1.0–1.5 wt%. At 1.5 wt%, the bonding strength is 1.07 MPa, which further decreases to 0.99 MPa at 2.0 wt%. The formaldehyde removal rate / purification efficiency reaches 91.1% at 1.5 wt%, but only slightly increases to 91.8% at 2.0 wt%, indicating a weakening marginal effect. Therefore, 1.3 wt% is selected as the preferred dosage in subsequent examples.

[0048] Example 5: Verification of Curing Agent Dosage Compensation

[0049] Each group employed a coating coupling process, varying only the amount of SB and NH4Cl added. Bond strength was determined according to GB / T 9846-2015, and the pH of the adhesive layer was determined according to GB / T 14074-2017. Gel time was used as a process reference indicator.

[0050] 0wt% 0.8wt% 356min 1.03MPa 5.0 1.3wt% 0.8wt% 417min 1.09MPa 6.1 1.3wt% 0.9wt% 392min 1.12MPa 6.2 1.3wt% 1.0wt% 363min 1.14MPa 6.3 1.5wt% 0.8wt% 448min 1.09MPa 6.0 1.5wt% 0.9wt% 407min 1.09MPa 6.2 1.5wt% 1.0wt% 381min 1.05MPa 6.3 2.0wt% 1.0wt% 426min 1.06MPa 6.5 2.0wt% 1.2wt% 371min 1.12MPa 6.6

[0051] The decomposition product Na₂CO₃ of SB raises the pH of the adhesive layer from 5.0 to approximately 6.3, inhibiting acid-catalyzed hydrolysis. Increasing the curing agent promotes full cross-linking of UF, compensating for the strength reduction caused by SB pore formation. When SB is 1.3 wt%, increasing the curing agent from 0.8 wt% to 1.0 wt% restores the bond strength from 1.09 MPa to 1.14 MPa.

[0052] Example 6: Purification Durability Test and High Concentration Validation

[0053] Test conditions: A 1m³ environmental chamber was set up according to JC / T 2761-2023, with a temperature of 23.0℃, relative humidity of 50.0%, and air exchange rate of 1 time per hour. Initial formaldehyde concentrations of 0.1 mg / m³ and 0.5 mg / m³ were set respectively. Purification durability was tested in multiple cycles according to JC / T 2761-2023, with each test cycle lasting 4 days, for a total of 6 cycles (24 days). The formaldehyde removal rate / purification efficiency at each time point is expressed as a specific test value.

[0054] Initial formaldehyde removal rate / purification efficiency 91.7% 87.6% 88.7% 83.7% Period 4 89.6% 83.7% 86.9% 80.8% Period 8 87.7% 80.8% 83.7% 77.9% Period 16 84.6% 77.9% 80.8% 74.0% Period 24 81.9% 73.2% 78.1% 70.4% Total attenuation 9.8 percentage points 14.4 percentage points 10.6 percentage points 13.3 percentage points Average daily decay rate 0.41% / day 0.60% / day 0.44% / day 0.55% / day

[0055] Group E maintained a lower formaldehyde removal rate / purification efficiency decay rate than Group C at both initial concentrations of 0.1 mg / m³ and 0.5 mg / m³. At the high concentration of 0.5 mg / m³, the difference in formaldehyde removal rate / purification efficiency between Group E and Group C widened from 5.0 percentage points to 7.7 percentage points, indicating that as formaldehyde concentration increases and catalytic oxygen consumption increases, the structural advantage of microporous oxygen supply becomes more significant.

[0056] Example 7: Optimization of Hot Pressing Process Parameters

[0057] 120℃ 0.6 MPa 2℃ / min 89.6% 1.12MPa 92.0% 125℃ 0.6 MPa 3℃ / min 91.7% 1.01MPa 94.0% 130℃ 0.7MPa 4℃ / min 92.7% 1.08MPa 96.0%

[0058] Optimal conditions: 125℃, 0.6 MPa, 3℃ / min, balancing formaldehyde removal rate / purification efficiency and adhesive strength. At 130℃, the SB decomposition rate is too fast, and some composite particles are too large, slightly increasing the damage to the continuous structure of the adhesive layer, resulting in a decrease in adhesive strength (1.08MPa vs 1.01MPa). However, the formaldehyde removal rate / purification efficiency slightly increases to 92.7% due to the increased micropores.

[0059] Example 8: 24-hour cold water immersion water resistance test

[0060] According to GB / T 9846-2015 Class III plywood standard, the wet bonding strength was tested after soaking in cold water at 20.0℃ for 24 hours; the pH of the adhesive layer was simultaneously determined according to GB / T 14074-2017.

[0061] A: Blank 1.01MPa 0.92MPa 92.0% 5.0 C: Manganese carbon only 1.03MPa 0.94MPa 92.0% 5.0 E: Enveloping coupling 1.01MPa 0.90MPa 90.0% 6.3

[0062] The wet bond strength of Group E was 0.90 MPa, slightly lower than Group A (0.92 MPa) and Group C (0.94 MPa), but still significantly higher than the requirement of ≥0.7 MPa for Class III plywood in GB / T 9846-2015. The wet bond strength retention rate of Group E was approximately 90.0%, indicating that the micropores formed by the coating coupling did not cause significant loss of water resistance; at the same time, the pH of the adhesive layer was 6.3 (near neutral), and Na2CO3 had a certain neutralizing effect on the residual HCl in the curing agent, which could reduce the risk of acid-catalyzed hydrolysis.

Claims

1. A formaldehyde-removing plywood with a microporous adhesive layer and a manganese-carbon composite material, comprising multiple layers of wood veneer and a microporous modified adhesive layer glued between the veneers, characterized in that: The microporous modified adhesive layer comprises a first urea-formaldehyde resin, manganese-carbon composite particles, a first curing agent, and a first flour. The manganese-carbon composite particles are core-shell structured particles, with a core of sodium bicarbonate particles and a shell layer of mixed resin coating the surface of the sodium bicarbonate particles. The mixed resin layer comprises manganese-carbon composite material, a second urea-formaldehyde resin, a second flour, and a second curing agent. The particle size of the composite particles is 200~800μm. The manganese-carbon composite material is activated carbon loaded with δ-MnO2, the δ-MnO2 loading is 2-5 wt% of the activated carbon mass, and the amount of manganese-carbon composite material added is 3-5 wt% of the total mass of the first urea-formaldehyde resin and the second urea-formaldehyde resin. The total amount of the first flour and the second flour is 30-40 wt% of the total mass of the first urea-formaldehyde resin and the second urea-formaldehyde resin. The amount of sodium bicarbonate added is 1.0~2.0 wt% of the total mass of the first and second urea-formaldehyde resins; The amount of the first curing agent added is 0.9~1.2 wt% of the total mass of the first and second urea-formaldehyde resins; In the mixed resin layer, the second flour accounts for 15% to 25% of the mass of the mixed resin layer, and the mass ratio of the mixed resin layer to the sodium bicarbonate is 5:1 to 15:1; the adhesive layer has a microporous structure formed by the decomposition and release of CO2 by the sodium bicarbonate during hot pressing. The amount of the second curing agent added is 0.5~1wt% of the second urea-formaldehyde resin.

2. The plywood according to claim 1, characterized in that: The solid content of urea-formaldehyde resin is 48%-55%, and the viscosity should be adjusted to 3000-5000 mPa·s before use.

3. The plywood according to claim 1, characterized in that: The viscosity of the urea-formaldehyde resin was adjusted to 3500-4500 mPa·s before formulation.

4. The plywood according to claim 1, characterized in that: The manganese-carbon composite material is coconut shell activated carbon supported on δ-MnO2.

5. The plywood according to claim 1, characterized in that: The mass ratio of the first urea-formaldehyde resin to the second urea-formaldehyde resin is 85:10 to 90:

10.

6. The plywood according to claim 1, characterized in that: Both the first curing agent and the second curing agent are ammonium chloride.

7. The plywood according to claim 1, characterized in that: The amount of manganese-carbon composite material added is 4 wt% of the total mass of the first urea-formaldehyde resin and the second urea-formaldehyde resin; the δ-MnO2 loading is 3.2 wt% of the mass of coconut shell activated carbon; the amount of sodium bicarbonate added is 1.0~1.5 wt% of the total mass of the first urea-formaldehyde resin and the second urea-formaldehyde resin; the mass ratio of the mixed resin layer to the sodium bicarbonate is 13:1; the second flour accounts for 17.6 wt% of the mass of the mixed resin layer; the total amount of the first flour and the second flour is 37 wt% of the total mass of the first urea-formaldehyde resin and the second urea-formaldehyde resin; the amount of the first ammonium chloride added is 1.0 wt% of the total mass of the first urea-formaldehyde resin and the second urea-formaldehyde resin.

8. A method for preparing plywood according to any one of claims 1-7, characterized in that, Includes the following steps: Step 1) Preparation of manganese-carbon composite material: Coconut shell activated carbon that has been pretreated by washing and drying is mixed with 0.04-0.06 mol / L potassium permanganate solution and ethanol. The molar ratio of ethanol to potassium permanganate is 1:1-3:

1. The mixture is reacted at 20-30℃ for 6-10 hours, filtered, washed and dried to obtain manganese-carbon composite material loaded with δ-MnO2. Step 2) Preparation of composite particles: First, the manganese carbon composite material obtained in step 1) is premixed with the second urea-formaldehyde resin and the second flour in a low-shear mixing device at an appropriate speed for 5-10 minutes. Then, sodium bicarbonate pore-forming agent is added and mixing is continued for 15-25 minutes to ensure that the mixed resin completely coats the sodium bicarbonate particles. The mixture is then dried at a low temperature of 40-50℃ to form composite particles with a particle size of 200-800μm. Step 3) Adhesive preparation: Add the composite particles obtained in step 2) and the first flour to the first urea-formaldehyde resin and stir evenly. Finally, add the curing agent and stir evenly. After preparation, seal the adhesive and store it at a low temperature of 10-15℃. Use it within 24 hours. Step 4) Applying adhesive, assembling, and pre-pressing: Apply adhesive to the veneer, with an amount of 180-250 g / m² on one side. Assemble the odd-numbered veneer layers with vertical grain and cold press at 0.6 MPa and room temperature for 2-3 hours. Step 5) Hot pressing: Heat to 125-130℃ at a heating rate of 2-4℃ / min, and hot press for 45min under a pressure of 0.6~0.7MPa. During the hot pressing process, sodium bicarbonate decomposes to produce CO2, which forms a microporous structure in the adhesive layer. Step 6) Cooling and warehousing of finished products: After hot pressing, the finished products are cooled to room temperature and then stored in the warehouse.

9. The preparation method according to claim 8, characterized in that: The hot pressing temperature in step 5) is 125℃, the pressure is 0.6MPa, and the heating rate is 3℃ / min.

10. The preparation method according to claim 8, characterized in that: In step (1), the particle size of coconut shell activated carbon is 80~150μm and the specific surface area is 1000m² / g; the mass ratio of activated carbon to potassium permanganate is 20:1.